QUANTITATIVE AND QUALITATIVE RESPONSE OF WHEAT TO PSEUDOMONAS FLUORESCENS RHIZOBACTERIA APPLICATION - I. Erdemci; H. Aktas; A. Eren (Journal of Animal and Plant Sciences, 2019)
Rhizobacterial application is efficient approach and process focusing less chemical fertilizers for increasing soil fertility and nutritional value of grains for different crops. This study investigated the effect of Pseudomonas fluorescens rhizobacterial application on the yield, yield components, grain quality and content of nutrition elements in wheat and in soil. Experiments were designed according to randomized complete block design with four replications in environmental conditions of Diyarbakir province, Turkey, during 2014 and 2015 growing seasons. Four treatments of Pseudomonas fluorescens rhizobacteria (control, seed inoculation, foliar application, seed + foliar) were used to investigate their effects on various aspects of wheat crop. Results of present study indicated that P. fluorescens rhizobacteria applications  significantly (P≤ 0.05) affected  grain yield,  Al, K, Mg, and Zn  content in grain,  total N, and  available P, K, Fe, and Mn elements in soil. The maximum grain yield was obtained from the combined application of seed inoculation + foliar application and showed 7% higher yield than in the control. Study indicated that application of rhizobacteria has positive effect on soil productivity, yield and nutritional quality of grains.
Keywords: Wheat; Pseudomonas fluorescens; rhizobacteria; seed inoculation; foliar application